Pengaruh Financial Literacy, Peers Influence, Self-Control, Religious Belief dan Parental Socialization Terhadap Saving Behavior pada Mahasiswa di Kota Batam - Fendy Cuandra; Desianti Desianti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The lack of public awareness about saving is still happening. So far, people's saving behavior is only done when there is a surplus of income after consumption is fulfilled. The fundamental problem faced by humans from birth is the human need to meet their daily needs. Human nature who is always dissatisfied with what they have achieved makes them have to try. There are many ways to do it, including setting aside or saving some of the results of consumption and preparing for the future. Therefore, it is necessary to instill the habit of saving from an early age in children so that their inexhaustible needs in the future can be minimized. This research was conducted on 410 students in Batam related to student’s savings habits. The results of the questionnaires were then processed using SPSS. The test results indicated that there is a significant positive relationship in all tested variables in accordance with the formulated hypothesis. The results of this study are expected to enrich research related to the interest in saving among students as the nation's next generation.